2009
DOI: 10.1590/s1516-89132009000600018
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic morphology and testis morphometry of captivity-bred Adult bullfrogs (Lithobates catesbeianus Shaw, 1802)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…The testes of both African catfish and Nile tilapia, observed in this present study to have tunica albuginea of loose connective tissues and the spermatic duct containing sperm cells, surrounded by connective tissue are in agreement with the earlier studies of Awaad et al (2014) in Nile tilapia and the pattern observed in most teleosts (Carlos and Matta, 2009). The African catfish and Nile tilapia, share the basic structures with other fishes (Meisner et al, 2000), avian (Friedlander and Parrish, 1997) and mammalian species (Ahmed et al, 2013).…”
Section: Histomorphologysupporting
confidence: 92%
“…The testes of both African catfish and Nile tilapia, observed in this present study to have tunica albuginea of loose connective tissues and the spermatic duct containing sperm cells, surrounded by connective tissue are in agreement with the earlier studies of Awaad et al (2014) in Nile tilapia and the pattern observed in most teleosts (Carlos and Matta, 2009). The African catfish and Nile tilapia, share the basic structures with other fishes (Meisner et al, 2000), avian (Friedlander and Parrish, 1997) and mammalian species (Ahmed et al, 2013).…”
Section: Histomorphologysupporting
confidence: 92%
“…The cells are located eccentrically with one to three nucleoli [118]. For example, Leydig cells are stored in cysts in Lithobates catesbeianus and bullfrogs have cells with a higher proportion of nuclei than cytoplasm [116]. The Sertoli cells in Physalaemus cuvieri are voluminous, elongated, and ovoid [119].…”
Section: Sertoli and Leydig Cellsmentioning
confidence: 99%
“…These interstitial cells are essential for spermatogenesis since they synthesize testosterone and other androgens [ 94 , 107 ]. The Leydig cells occupy approximately one-quarter of the interstitial tissue [ 116 ]. They are either detached or in groups near the blood vessels [ 117 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the Neotropics, little has been studied about the processes of spermatogenesis and spermiogenesis in this group of organisms (Carezzano et al, 2013). It has been evidenced that the majority of anurans present a testis with cystic cellular organization, although with differences in aspects such as pigmentation and thickness of the albuginea tunic (Carlos & Matta, 2009;Guillama et al, 2014). Dark pigmentation in the testes has been described in some species and is caused by cells called melanocytes that are randomly distributed in the albuginea tunic and the interstitium (Aoki et al, 1969;Oliveira et al, 2002;Guillama et al, 2014).…”
mentioning
confidence: 99%